[Workers conducting repairs at Point Lisas] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Workers conducting repairs on the sugar conveyor at Point Lisas shipping terminal.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago